2010
DOI: 10.1007/s11010-010-0673-5
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms within functional regions of genes implicated in insulin action and association with the insulin resistant phenotype

Abstract: Type 2 diabetes and insulin resistance (IR) are characterized by severe anomalies in genes expression rate including genes involved in insulin signal transduction. Post-transcriptional regulation of gene expression is crucial for many physiological processes and is mediated mainly by untranslated region (UTR). Present study concentrated on the search for correlation between single nucleotides polymorphisms in UTRs of the INSR, PIK3R1, PTPN1, and SLC2A4 genes and IR. 130 unrelated diabetic patients and 98 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…However we did not find any association between INSR rs1052371 genotypes and alleles and CRC risk. Malodobra et al (2011) also reported no association between the SNP and the insulin resistant. Obtained results need to be verified on larger number of subject and replicated within distinct population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However we did not find any association between INSR rs1052371 genotypes and alleles and CRC risk. Malodobra et al (2011) also reported no association between the SNP and the insulin resistant. Obtained results need to be verified on larger number of subject and replicated within distinct population.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally there are some inconsistent results about association between IRS2 haplotypes and obesity risk (Lautier et al, 2003). Some previous studies conducted to investigate the effect of IGF-I, INSR and IRS2 gene polymorphisms on insulin resistant and type 2 diabetes mellitus (FloresMartínez et al, 2004;Bodhini et al, 2007;Vella et al, 2008;Baroudi Ouederni et al, 2009;Malodobra et al, 2011). So far, the associations of insulin pathway gene polymorphisms with prostate and breast cancer have been studied intensively but their results were inconsistent (Ho et al, 2003;Neuhausen et al, 2005;Deming et al, 2007;Deming et al, 2008;Sarma et al, 2008;Xuefen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, we found that 59 candidate genes have been connected to SCZ [34][35][36][37][38], 77 candidate genes have been linked to T2D [39][40][41][42][43], while 25 candidate genes [44][45][46][47][48][49] have been implicated to both SCZ and T2D with various studies (Additional file 5). Totally, 161 candidate genes (~45% of all candidate genes) have been related to either SCZ or T2D or both diseases with various experimental approaches, further proving the rationale of "function association" in the application of disease related gene inference.…”
Section: New Candidate Risk Gene Inferencementioning
confidence: 90%
“…These data suggested that SNPs in non coding but functional genome regions play important role in common human systemic diseases. In our previous study we have shown difference in genotype distribution of two SNPs located in 3'UTR of INSR gene and PIK3R1 gene and its correlation with insulin resistant phenotype (Malodobra et al, 2011). It has been shown that G/G genotypes of two SNPs (rs3756668 of PIK3R1 gene and rs3745551 of INSR gene) correlated with BMI, insulin resistant ratios (HOMA-IR and QUICKI) and increased risk of IR .…”
Section: Snps In Microrna Genes/ Microrna Target Sites and Insulin Rementioning
confidence: 94%